Combined Application of Bevacizumab and Mitomycin C or Bevacizumab and 5-Fluorouracil in Experimental Glaucoma Filtration Surgery - Lei Zuo; Jianhong Zhang; Xun Xu (Journal of Ophthalmology)
The present study aimed at observing the effect of a single subconjunctival injection of bevacizumab (BVZ) combined with 5-fluorouracil (5-Fu) or mitomycin C (MMC) on the antiscarring effect of glaucoma filtration surgery (GFS). The inhibitory effect of combined BVZ and 5-Fu in retinal pigment epithelial cells on vascular endothelial growth factor (VEGF) levels was demonstrated through in vitro experiments. Combined BVZ and 5-Fu and combined BVZ and MMC inhibited cell cycle, induced apoptosis, and inhibited human umbilical vein endothelial cell migration. Also, the cytotoxicity of combined BVZ and 5-Fu was lower. In animal experiments, the observation of filtering bleb survival, hematoxylin and eosin and Masson staining of filtering bleb scars, and mRNA expression levels of fibrosis markers in filtering blebs showed that combined BVZ and 5-Fu had a better antiscarring effect compared with single drugs; however, the antiscarring effect of combined BVZ and MMC was not significantly different from MMC. Therefore, the findings of this study provided more reference for the clinical use of adjuncts to inhibit scarring after GFS and helped understand the regulatory effect of combined anti-VEGF antibody BVZ and antimetabolites on wound healing more comprehensively.